5.3k views
1 vote
( 3b - 4b ) ²

with explanation​

2 Answers

5 votes
Answer: b^2

Step-by-step explanation:
( 3b - 4b ) ² with explanation​-example-1
User Avinash B
by
5.5k points
2 votes

Answer:

b^2

Step-by-step explanation:

(3b-4b)^2

=(-b)^2

we know that,

- * - =+

minus(-) * minus(-) = +

By using formula to the f

given equation is;

( 3b - 4b ) ²

We know that,

(a-b)^2 =a^2-2ab+b^2

Soo,

=9b^2 - 2*3b*4b +16b^2

=9b^2-2*3*4b^2+16b^2

=9b^2+16b^2-24b^2

=25b^2-24b^2

=b^2

User Guy Levy
by
5.1k points